Antimalarial bednet protection of children disappears when shared by three or more people in a high transmission setting of western Kenya. Issue 3 (10th September 2018) - Tamari, Noriko; Minakawa, Noboru; Sonye, George O.; Awuor, Beatrice; Kongere, James O.; Munga, Stephen; Larson, Peter S.
Abstract: A sizeable proportion of households is forced to share single long-lasting insecticide treated net (LLIN). However, the relationship between increasing numbers of people sharing a net and the risk for Plasmodium infection is unclear. This study revealed whether risk for Plasmodium falciparum infection is associated with the number of people sharing a LLIN in a holoendemic area of Kenya. Children ⩽5 years of age were tested for P. falciparum infection using polymerase chain reaction. Of 558 children surveyed, 293 (52.5%) tested positive for parasitaemia. Four hundred and fifty-eight (82.1%) reported sleeping under a LLIN. Of those, the number of people sharing a net with the sampled child ranged from 1 to 5 (median = 2). Children using a net alone or with one other person were at lower risk than non-users (OR = 0.29, 95% CI 0.10–0.82 and OR = 0.47, 95% CI 0.22–0.97, respectively). On the other hand, there was no significant difference between non-users and children sharing a net with two (OR = 0.88, 95% CI 0.44–1.77) or more other persons (OR = 0.75, 95% CI 0.32–1.72). LLINs are effective in protecting against Plasmodium infection in children when used alone or with one other person compared with not using them. Public health professionals should inform caretakers of the risks of too many people sharing a net.